Landscape configuration is the primary driver of impacts on water quality associated with agricultural expansion. (11th July 2016) - Chaplin-Kramer, Rebecca; Hamel, Perrine; Sharp, Richard; Kowal, Virgina; Wolny, Stacie; Sim, Sarah; Mueller, Carina
Abstract: Corporations and other multinational institutions are increasingly looking to evaluate their innovation and procurement decisions over a range of environmental criteria, including impacts on ecosystem services according to the spatial configuration of activities on the landscape. We have developed a spatially explicit approach and modeled a hypothetical corporate supply chain decision representing contrasting patterns of land-use change in four regions of the globe. This illustrates the effect of introducing spatial considerations in the analysis of ecosystem services, specifically sediment retention. We explored a wide variety of contexts (Iowa, USA; Mato Grosso, Brazil; and Jiangxi and Heilongjiang in China) and these show that per-area representation of impacts based on the physical characterization of a region can be misleading. We found two- to five-fold differences in sediment export for the same amount of habitat conversion within regions characterized by similar physical traits. These differences were mainly determined by the distance between land use changes and streams. The influence of landscape configuration is so dramatic that it can override wide variation in erosion potential driven by physical factors like soil type, slope, and climate. To minimize damage to spatially-dependent ecosystem services like water purification, sustainable sourcing strategies should not assume a direct correlation between impact and area but rather allow for possible nonlinearity in impacts, especially in regions with little remaining habitat and highly variable hydrological connectivity.